Large-scale Synthesis of CdTe Quantum Dots in Aqueous Phase - Toan, Pham Song; Thien, Trinh Duc; Liem, Nguyen Quang (Communications in Physics, 2012)
In this paper, we present the systematically experimental results on the influences of pH of the reaction medium, molar ratio of the precursors on the synthesis in aqueous phase of CdTe quantum dots (QDs) and CdTe/CdS QDs with core/shell structure. Under optimal synthesis conditions, water-soluble CdTe and CdTe/CdS QDs have been prepared that exhibit very strong photoluminescence peaking in the spectral range between 520 nm and 650 nm with narrow full width at half maximum (\(32\) nm in the short-wavelength emission case); depending on the emission range, most samples however exhibit the high luminescence quantum yields (\(40\)%). Moreover, the synthesis in aqueous phase shows some additional advantages: it is possible to prepare high quality CdTe QDs in large-scale (up to gram/reaction) with low cost, less toxic and short production time.